Seed Systems and Crop Management Community of Practice: Are Learning Journeys Useful? - International Potato Center (2016)
Peer-to-peer technical engagement has been increased through conducting eight learning journeys as part of the seed system community of practice meetings. The learning journeys provide opportunities for informal knowledge sharing, networking and cementing the bonds between members.